Strengthening the Maritime Security Legal Framework through the Implementation of the ISPS Code for the Protection of Ships and Port Facilities at Bitung Port - Agus Arifianto; Effendy Lod Simanjutak (Journal Customary Law, 2026)
This study aims to analyze the legal regulations on maritime security in the implementation of the ISPS Code and formulate ideal legal reforms to strengthen the protection of ships and port facilities at Bitung Port. The research method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that the regulations in Law Number 17 of 2008 concerning Shipping have not comprehensively adopted the ISPS Code standards, resulting in a gap between norms and implementation in the field, including weaknesses in aspects of supervision, resources, and institutional coordination. Therefore, legal reconstruction and reform are needed through regulatory harmonization, institutional strengthening, and technology integration to realize an effective maritime security system in accordance with international standards.